Subclinical cerebrovascular cognitive function, and mood changes in patients with systemic lupus erythematosus - Ghaydaa A Shehata (Dove Medical Press, 2010)
Ghaydaa A Shehata1, Mohamed I Abdel-Kareem2, Abd ellah N Yassin4, Abdel Ahamid R El Adl31Department of Neurology, Faculty of Medicine, Assiut University, Assiut, Egypt; 2Department of Rheumatology, Physical Medicine and Rehabilitation Faculty of Medicine, 3Department of Internal Medicine, Faculty of Medicine, Al-Azhar University, Assiut, Egypt; 4Department of Diagnostic Radiology, Faculty of Medicine, Al-Azhar University, Cairo, Egypt Objective: To estimate the prevalence of neuropsychiatric disorders, cerebral atherosclerosis in patients with systemic lupus erythematosus (SLE) and explore the relation between transcranial duplex findings of different intracranial vessels with neuropsychiatric affect, and Systemic lupus erythematosus disease activity index (SLEDAI).Methods: Twenty-six consecutive SLE patients were evaluated for neurological and psychiatric disorders. Another 26 subjects matched with respect to age, sex, education, and socioeconomic status formed the control group. SLE disease activity was assessed by the SLEDAI. For each participant, a complete medical history was obtained and clinical, laboratory, and neurophysiological examinations, magnetic resonance imaging of the brain, transcranial duplex for intracranial vessels, and psychometric evaluations were performed. For the psychometric evaluation, we used the Modified Mini-mental State Examination and Cognitive Assessment Scale Inventory to assess cognitive function, and Hamilton Depression Rating Scale and Hamilton Anxiety Scale to assess symptoms of depression and anxiety.Results: Anxiety in 65.4% is the most prevalent manifestation followed by depression in 57.7%, headache in 38.5%, peripheral neuropathy in 26.9%, seizures in 23.1%, psychosis in 19.2%, radiculopathy and dementia in 15.4% for each, myositis in 11.5%, and stroke in 7.7%. There was a significant increased mean velocity and decreased pulsatility index of most studied intracranial vessels in both patient groups than in the control group. There was significant negative correlation between SLEDAI and transcranial Doppler findings in the pulsatility index of medial circumflex artery and procoagulant activity.Conclusion: Neurological disorders, cognitive impairment, depression, anxiety, psychosis and cerebrovascular changes detected by transcranial Doppler ultrasound are common in SLE.Keywords: SLE, SLEDAI, cognitive function, depression, anxiety, neurological disorders, TCD, cerebrovascular changes